PENGEMBANGAN MEDIA PEMBELAJARAN MINIATUR UNTUK MENINGKATKAN PEMAHAMAN KONSEP IPA PADA MATERI TATA SURYA DI KELAS VI SDN SINDANGMULYA 01 - Nurhamidah; Ira Restu Kurnia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Nurhamidah Developing Miniature Learning Media to Improve Understanding of Science Concepts in Solar System Material in Class VI SDN Sindangmulya 01. Bachelor of Education, Pelita Bangsa University Supervisor: (Ira Restu Kurnia, S.Pd., M.Pd). By developing Miniature Learning Media, it can improve the understanding of science concepts in solar system material in class VI of SDN Sindangmulya 01. This study aims to develop a design for miniature solar system learning media, test the feasibility of the media, and describe teacher responses to the developed learning media. The method used is Research and Development (R&D), especially with the ADDIE model, which consists of five stages, namely the analysis stage, design stage, development stage, implementation stage, and evaluation stage. In this study, data collection techniques were carried out through several methods designed to ensure the validity and effectiveness of miniature solar system learning media by conducting a feasibility test by material expert validators, media expert validators, language expert validators and student responses. The results of the feasibility test of the miniature solar system learning media showed very positive results based on assessments from various material expert validators getting a very feasible category with a percentage of 92%, so that the miniature solar system learning media is included as